A novel system for large-scale gene expression analysis: bacterial colonies array - Barsalobres-Cavallari, C.; De Rosa Junior, V.; Nogueira, F.; Ferro, J.; Di Mauro, S.; Menossi, M.; Ulian, E.; Silva-Filho, M. (Springer, 2006)
In the present work, we report the use of bacterial colonies to optimize macroarray technique. The devised system is significantly cheaper than other methods available to detect large-scale differential gene expression. Recombinant Escherichia coli clones containing plasmid-encoded copies of 4,608 individual expressed sequence tag (ESTs) were robotically spotted onto nylon membranes that were incubated for 6 and 12 h to allow the bacteria to grow and, consequently, amplify the cloned ESTs. The membranes were then hybridized with a beta-lactamase gene specific probe from the recombinant plasmid and, subsequently, phosphorimaged to quantify the microbial cells. Variance analysis demonstrated that the spot hybridization signal intensity was similar for 3,954 ESTs (85.8%) after 6 h of bacterial growth. Membranes spotted with bacteria colonies grown for 12 h had 4,017 ESTs (87.2%) with comparable signal intensity but the signal to noise ratio was fivefold higher. Taken together, the results of this study indicate that it is possible to investigate large-scale gene expression using macroarrays based on bacterial colonies grown for 6 h onto membranes.